Approaches of european union and turkey to abuse of dominant position through the methods other than pricing - Semiz, Selen Egeli (My University, 2008)
Ticari hayatta faaliyette bulunan teşebbüslerin nihai hedefi, rakiplerine göre daha fazla kâr elde etmek, belirli bir ekonomik güce sahip olmak ve piyasada hakim konuma gelmektir. Hakim durumda olmak, hiç şüphesiz, ticari teşebbüsün başarılı olduğunun bir göstergesidir. Rekabet kuralları da elbette hakim durumda bulunmayı yasaklamamaktadır. Ancak, bununla birlikte, teşebbüsün bu hakim durumunu rakiplerinin, müşterilerinin, tüketicilerin ve genel olarak piyasanın zararına yol açacak şekilde kötüye kullanması, gerek Avrupa Birliği’nde gerekse Türkiye’de düzenlenen rekabet kuraları ile yasaklanmıştır. Kötüye kullanma, değişik şekillerde görülebilmektedir. Avrupa Birliği ve Türkiye’de hakim durumun kötüye kullanılma şekilleri ve bunun sonuçları, Avrupa Topluluğu Antlaşması’nın 82. maddesi ve Türkiye’de halihazırda uygulanmakta olan 4054 sayılı Rekabetin Korunması Hakkında Kanun’un 6. maddesi çerçevesinde düzenlenmiş ve mahkeme kararları nezdinde geliştirilmiştir. Bu çalışmanın konusu, Avrupa Birliği ve Türkiye’de, hakim durumun fiyatlama dışındaki yöntemlerle kötüye kullanılması hallerinin incelenmesini kapsamaktadır.

The final aim of the undertakings operating in the commercial life is to gain profit more than their competitors, to have a specific economical power and to be in dominant position in the market. To be in a dominant position, without any doubt, is an indication that the commercial undertaking is successful. Of course, the competition rules do not prohibit being in a dominant position. However, nevertheless, to abuse the dominant position by the undertaking as to cause damage to its competitors, customers, consumers and in general the market is prohibited through competition rules regulated both in European Union and in Turkey. Abusing can be seen as different forms. The types and consequences of abuse of dominant position are regulated in the framework of the Article 82 of EC Treaty and the Article 6 of the Act on Protection of Competition numbered 4054 currently being applied in Turkey and is developed under the court decisions. The subject of this study covers the analysis in European Union and in Turkey, the aspects of abuse of dominant positions through the methods other than pricing.
Keywords: Avrupa Birliği_Türkiye_Hukuk; Rekabetin Korunması Hakkında Kanun